2018
DOI: 10.2460/javma.253.10.1289
|View full text |Cite
|
Sign up to set email alerts
|

Effects of the use of silver-coated urinary catheters on the incidence of catheter-associated bacteriuria and urinary tract infection in dogs

Abstract: OBJECTIVE To determine the effects of silver-coated versus standard silicone urinary catheters on the incidence of catheter-associated bacteriuria (CAB) and catheter-associated urinary tract infection (CAUTI) in dogs. DESIGN Randomized controlled clinical trial. ANIMALS 36 dogs requiring urinary bladder catheterization for ≥ 24 hours. PROCEDURES Dogs were randomly assigned to receive a silver-coated or non–silver-coated (control) silicone Foley catheter. Urine samples for cytologic examination and bacterial cu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
9
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
4
2
2

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(9 citation statements)
references
References 18 publications
0
9
0
Order By: Relevance
“…Another randomized study of 36 dogs was conducted where half were given a silver-coated catheter and the other half given an uncoated catheter. No statistical difference in the incidence of CAUTI was found, but the mean time to bacteriuria was shorter for the silver-coated group [84].…”
Section: In Vivo Studiesmentioning
confidence: 72%
See 1 more Smart Citation
“…Another randomized study of 36 dogs was conducted where half were given a silver-coated catheter and the other half given an uncoated catheter. No statistical difference in the incidence of CAUTI was found, but the mean time to bacteriuria was shorter for the silver-coated group [84].…”
Section: In Vivo Studiesmentioning
confidence: 72%
“…Silver ions are the most popular clinically tested and available coating for urinary catheters yet the effectiveness of them is still debatable due to vast differences in outcomes in vitro, in animal models and in clinical trials studies [34,51,[72][73][74][75][76][77][78][79][80][81][82][83][84][85][86]. The mechanisms by which silver is toxic to bacteria include disruption of the membrane, proteins, and by inducing oxidative stress through the release of silver ions into the bladder [15].…”
Section: Silver Ionsmentioning
confidence: 99%
“…28 However, an in vivo animal test in dogs of seven days found that there was no clinical benefit for these catheters over standard non antimicrobial catheters. 29…”
Section: Introductionmentioning
confidence: 99%
“…[3][4][5][6] In people, the daily risk of bacteriuria with an indwelling urinary catheter is 3% to 10%, 7,8 and incidence of catheter-associated UTI among hospitalized dogs has been reported to be 10% to 19%. 6,[9][10][11] These observations highlight the need for alternative methods to measure UBV other than urinary catheterization.…”
mentioning
confidence: 99%
“…In dogs, formulations derived from 2-dimensional (2D) ultrasound measurements have provided acceptable estimates of UBV and for calculating URV to assess UOP. 1,[8][9][10][11][12][13] Formulas derived from the human medical literature have inconsistencies associated with variations in bladder shape and size. 2,[12][13][14][15] Most recently, use of a simple formula of length (L) × width (W) × height (H) × 0.52 has provided the best estimation of bladder volume in people using 2D ultrasound B-mode images compared to other formulas.…”
mentioning
confidence: 99%